Models of educational provision in the United Kingdom's university museums: resources for the development of Malaysian university museums / Wahiza Abdul Wahid - Abdul Wahid, Wahiza (2018)
Museums have been a part of human history over two thousand years but they were not always like the one we visit today. Museum as an institution is always expected to serve the public, to be non-profit making, open to all and to deliver information through exhibitions for the purpose of education, general knowledge, conservation, research, communication. Apart from being a place where knowledge can be transferred, museum serves for leisure based on the artifacts assembled and excavated from various civilizations from all over the world. The functions and role of museums nowadays are developing positively over the past few decades throughout the world. There is an overwhelming growth of museums around the world at present. A growing concern regarding the lack of research in the museum studies field is obvious and this should be looked into. This study intends to provide information and data in a mission to upgrade the museum sector in Malaysia, which is continuously in its transitional period. Due to an increase of awareness among Malaysians of the value of their Malaysian heritage, this research is carried out with hope that it will act as a benchmark for the future of museums in Malaysia. Museums in the UK are historically different in many aspects, for example funding and their educational provisions. Overall, this study is set out to identify how the knowledge transfer is being practiced in the Malaysian museums, with three references of museums in the UK as benchmarks, and three most prominent university museums in Malaysia. This research is also carried out to investigate what strategies and methods are employed in developing and running the educational activities in the university museums chosen for the case studies and to establish the findings that may be possible to be implemented in upgrading the museum sectors in Malaysia. The whole process of this study begins with the selection of case studies for benchmarking and case studies for the purpose of implementation. The employment of primary methods are based on personal interviews, surveys and observation. The findings to this research are analyzed through the cross case studies, questionnaires delivered to the selected respondents and information providers, mainly the interviewees involved. Findings are more concerned and focused on the educational programs and activities, and at the same time, project on the possible factors and methods that will welcome more returners to the university museums in Malaysia. This is the first study of its kind on this topic that focuses mainly on the educational provisions in Malaysian university museums. Most researches and written articles are mainly emphasizing on archaeological findings, the layouts and collections of museums. This research describes the current state of museums, particularly the university museums in Malaysia and the UK and aims to contribute to the future development of the museum field in Malaysia. Three of what is considered to be among the well-known university museums of the UK: The Ashmolean, Manchester Museum and the Petrie are chosen for the benchmarking while three most active Malaysian university museums: Muzium Seni Asia, Muzium dan Galeri Tuanku Fauziah and Muzium Pendidikan Nasional are taken as the case studies to see the potential of performing better in regard to the educational provision. Finally, the knowledge gained from this research will help to provide a foundation for future researchers interested in the development of museum studies in Malaysia.